Karaeng in Service - Habbodin, Muhtar; Mujiburrohman, M. Alexander (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
This article explores the conduct of local politics of the karaeng group serves and citizens in Kampala Village, Arungkeke District, Jeneponto Regency, South Sulawesi. The Karaeng group has the highest status in South Sulawesi’s social structure when compared to the Daeng and Ata groups. Even though the Karaeng group is the ruling elite, this does not mean that its citizens always serve them. However, it is quite the opposite. The method used is a case study. The choice of case studies is based on the idea that cases are limited, actual, and unique. Meanwhile, the data collection mechanism is by combining interviews and literature study. When the data has been collected, the next step is to analyze it critically. Field findings indicate that the karaeng group uses two instruments to provide services to their citizens. First, large land ownership. Residents are free to use this land for living and housing purposes free of charge. Second, position as an instrument to help and serve the needs of its citizens. Proper use of land and positions strengthens the power base of the karaeng group as a traditional elite and as the ruling elite in Kampala Village. These findings confirm that political changes at the village level require the karaeng group to adapt to remain powerful through the choice to provide services to the community. In this way, the Karaeng group has a stronger position in front of its citizens.